Manual de procedimientos contables basado en las NIIF´S 1 y 9 para la empresa de transporte Arroyo & Naranjo Trans GDA S.A., parroquia Guanujo, cantón Guaranda, provincia de Bolívar, primer semestre del año 2023 - Quillupangui Riofrio, Maria Fernanda (2024)
The investigation arises due to the lack of a manual of accounting procedures for the precise recording of information and support of the process that was carried out day by day in the accounting area of the company Transporte Arroyo & Naranjo Trans GDA S.A. In this sense, the primary objective was aimed at developing a manual based on International Financial Reporting Standards (IFRS) 1 and 9 applicable to the accounting area, an initiative focused on optimizing the effectiveness of transactions in accordance with current regulations. For this purpose, a non-experimental study was used through which the interview was applied to the president and the accountant/human resources, the survey to the accounting assistant and the person in charge of accounting/administration; In addition, the SWOT and observation of the accounting area in its natural state were carried out. Based on the results obtained, it was confirmed that it is essential to design an accounting procedures manual and guarantee its adequate implementation by applying the IFRS regulations, since it not only contributes to improving accounting management, but also aligns the company with international standards and, therefore,